LCA and wild animals: Results from wild deer culled in a northern Italy hunting district. (20th January 2020) - Fiala, Marco; Marveggio, Davide; Viganò, Roberto; Demartini, Eugenio; Nonini, Luca; Gaviglio, Anna
Abstract: Although the research of innovative and sustainable environmental alternatives to meat consumption is increasing, little attention has been given to hunting activity, which has traditionally provisioned food products from wild animals. Given this gap, the present study aims to quantify the environmental impacts of wild red deer culling ( Cervus elaphus ) through selective hunting in a mountainous Italian district, adopting a cradle-to-gate life cycle assessment (LCA) approach. Nine impact categories are evaluated using the International Reference Life Cycle Data System (ILCD) v1.09 impact assessment method, with climate change filling a special role. The results highlight that the long distances covered by the hunters to cull wild red deer is the hotspot of the supply chain representing almost 85% of the impact in every considered impact categories. Focusing on climate change, the outcomes show that the emissions of greenhouse gases (GHGs) per functional unit (4.85 kg CO2eq ) are largely influenced by the hypothesis considering the wild red deer as an elementary flow entering the system and, thus, not including enteric methane emissions. In this case, the hunted red deer meat appears to be an environmentally sustainable alternative to conventional beef. The representativeness of the findings has to be increased both within the same species and in association with other wild ungulates (e.g., roe deer, wild boar or chamois) to better understand the potential role of traditionally hunted wild products in more sustainable diets. Graphical abstract: Image 1 Highlights: The environmental burdens of a hunting supply chain have been investigated. Wild red deer is considered as an elementary flow entering the system. The distance covered by hunters for hunting represents the environmental hotspot (85%). Wild red deer can not be considered as a zero-impact food.